INCREASING STUDENTS’ GRAMMAR SKILLS USING DESCRIPTIVE TEXT: CLASSROOM ACTION RESEARCH AT SMAN 1 PAITON - Fabela, Ifa Aprilia; Tirmidi, Tirmidi; Fatmawati, Surya Dewi (Jurnal Review Pendidikan dan Pengajaran, 2025)
By implementing a learning strategy that emphasizes descriptive texts in class X at SMAN 1 Paiton, this study aims to improve students' skill English grammar. The two-cycle approach used in this study, namely Classroom Action Research, includes planning, implementing actions, observing, and reflecting in each cycle. Using descriptive techniques with quantitative and qualitative approaches, the data collected through writing tests, observations, interviews, and documentation were analyzed. The results of the study showed a significant improvement in students' language skills. With an increase in authorization from 31.4% to 91.4%, the average student score increased from 65.8 in the pre-cycle to 83.4 in Cycle II. Students became more active and reflective in their writing projects, thereby developing a more positive attitude towards learning. Thus, the application of descriptive text learning has proven to be quite successful in improving students' contextual and sustainable language competence.